MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN MELALUI MEDIA KARTU KATA BAGI ANAK LAMBAT BELAJAR - Misdar - Misdar (Jurnal Penelitian Pendidikan Khusus, 2013)
The purpose of this study were: 1) describe the implementation process of learning to improve reading skills using the word card words and 2) prove the said media card can improve word reading skills in children studying in class I slow SD No.. 14 Koto Panjang Pauh Padang. Type of research is a classroom action research (classroom action research) with two cycles performed in the form of collaboration with colleagues. Subjects were three children, slow learners (I, G and Iq) and one teacher. Data were collected through an oral test and analyzed qualitatively and quantitatively. The results showed that 1) the learning process in improving reading skills through the medium of the word card words do two cycles. Cycle I and Cycle II made ​​six (6) meetings. Each cycle begins with the planning, implementation (initial activity, core and end), observation, and analysis and reflection. 2) The results of the study proved that the child's ability to read words increased. It proved: results asessmen berkonsonan word reading ability [b, p] I gained (20%), G (10%) and Iq is (15%). After learning the media card in the first cycle capability word I to (100%), G (85%) and IQ (95%). In addition, the ability to read words I berkonsonan [d] when asessmen (20%), G (15%) and IQ (15%). After learning the word card pda second cycle capability I also (100), G (90%) and IQ (100%). It was concluded that the media card is the word slowly improving reading skills kids learn. Advised on the school, teachers and researchers can use the media next to the word cards to improve reading skills more.